(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
This paper analyzes the academic, administrative and regulatory transformation process which took place in the Michoacana University from 1971 to 1986 under the modernizing project of higher education implemented by the President Luis Echeverría Álvarez and maintained, with certain variables, by the following presidents José Lopez Portillo and Miguel De La Madrid Hurtado. The purpose of that project was to modernize the University in order to adapt it to the demands of the new stage of the economical development of the country and to make it the engine of the industrial development by forming the necessary human resources. The project implied to overpass the traditional university schema and to structure the curricula keeping in mind the production needs. In order to do that, the Federal Government, through the ANUIES, adopted the departmental model used in the United States. The Michoacana University received the necessary money to put it into practice. However, the American model crashed against the university traditional structure. Therefore, it was difficult to change.